If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27 + -7x = -6x Solving 27 + -7x = -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 27 + -7x + 6x = -6x + 6x Combine like terms: -7x + 6x = -1x 27 + -1x = -6x + 6x Combine like terms: -6x + 6x = 0 27 + -1x = 0 Add '-27' to each side of the equation. 27 + -27 + -1x = 0 + -27 Combine like terms: 27 + -27 = 0 0 + -1x = 0 + -27 -1x = 0 + -27 Combine like terms: 0 + -27 = -27 -1x = -27 Divide each side by '-1'. x = 27 Simplifying x = 27
| x^2-4x+4-75=0 | | 3=33-11 | | -v+1=4 | | -2r-15=8r-7r | | 6(-6x-4)=-60 | | 0.25(8y+4)-17=-0.5(2y-8) | | 2(4x+8)=3(2x-10) | | 1/4(8y+4)-17=-1/2(2y-8) | | 3(x+3)=5x-7 | | 4/35=h/50 | | 12x+15= | | -4(8-5n)+8=-1 | | Y=8X-70 | | -73+11y+8=4(4y-5)-5 | | 12+2d=3d+3 | | 3/9=x/3 | | 56-k=13 | | y+5-4yF=10 | | 2Y=8X-70 | | 18x-2(3x+5)=4(2x-8) | | 8w-4n=w | | -1/4(2-8) | | -2b+6=10 | | 4=2(3x-5)+15x | | -1/4(2y-8) | | 6/-3=7 | | 81/4-51/16 | | y=1/3x+b | | 2/3+1/2x+4+2x-1/3x-1/2 | | 1=0-x | | 4y=2X+7 | | 15x-38+2x-54=2(5x-3)+48 |